Channel-resolved molecular Auger spectroscopy. Issue 15 (January 2020) - Ablikim, U; Forbes, R; Bomme, C; Osipov, T; Xiong, H; Bilodeau, R; Kilcoyne, D; Rudenko, A; Holland, D M P; Berrah, N; Rolles, D
Synopsis: Molecular Auger spectra typically consist of many overlapping lines that are hard or impossible to resolve experimentally even with highest-resolution electron spectroscopy techniques. Since molecular Auger energies depend on non-adibatatic dynamics, they can also be difficult to calculate precisely, such that the assignment of molecular Auger transitions is often ambiguous. Here we show that by measuring Auger-electron multi-ion coincidences, we can disentangle the spectra into the contributions from specific ionic final states, which helps significantly with their interpretation and assignment.